2009
DOI: 10.1590/s1808-86942009000400013
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 and p53 correlation prognostic value in squamous cell carcinomas of the oral cavity and tongue

Abstract: Epi dermoid carcinomas represent from 90% to 95% of oral cavity malignant neoplasias, making up 13,470 cases/ year. Aims: To correlate p53 and Ki-67 expressions in mouth and tongue carcinomas with lymph node status, gender, histological grade, tumor volume and pathological stage. Materials and Methods:We carried out a retrospective study of 28 cases of mouth and tongue epidermoid carcinomas. They were submitted to immunohistochemical study in order to check the expression of p53 and Ki-67 antibodies and statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 21 publications
2
25
0
1
Order By: Relevance
“…Moreover, on comparing mean Ki-67 LI in the two groups of lymph node status for each grade of carcinoma, it was found that subjects with positive lymph node metastasis had comparatively higher mean Ki-67 LI than subjects with negative lymph node metastasis (Table 3). These observations were in consonance with the study by Motta et al 23 Thus, it may be implicated that tumors with a high cell PI (such as the mean Ki-67 LI) may indicate a potential for these tumors to metastasize.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, on comparing mean Ki-67 LI in the two groups of lymph node status for each grade of carcinoma, it was found that subjects with positive lymph node metastasis had comparatively higher mean Ki-67 LI than subjects with negative lymph node metastasis (Table 3). These observations were in consonance with the study by Motta et al 23 Thus, it may be implicated that tumors with a high cell PI (such as the mean Ki-67 LI) may indicate a potential for these tumors to metastasize.…”
Section: Discussionsupporting
confidence: 91%
“…It means that p53 expressions in those squamous cell carcinoma cases of oral cavity were correlated with a poor prognosis (grade III). This finding is in accordance with an opinion of Motta et al 10 stating that there is a correlation between p53 and a poor prognosis in oral cavity squamous cell carcinoma. p53 expressions in grading I indicates a highly significant correlation (p<0.01) due to the low expression distribution (4 cases) and the weak intensity (4 cases) on histopathological grading I.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with a research conducted by Rodrigues et al showing that there is no correlation between immunohistochemical p53 and histopathological grading in predicting prognosis for 30 cases of squamous cell carcinoma of larynx. 13 Similarly, another research conducted by Motta et al 10 also shows that there is no significant correlation between p53 and histopathological grading in predicting prognosis for 28 cases of squamous cell carcinoma of oral cavity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…therefore, the presence of Ki-67 is considered to be a 'proliferation index' of tumors (39). In oral cancers, patients with tumors with high positivity (92%) or lymph node metastasis had a poor outcome (40), and many studies indicated that Ki-67 could be an important prognostic factor (41)(42)(43)(44). similarly, 92% of subjects showed Ki-67 expression in our study.…”
Section: Discussionmentioning
confidence: 99%